Competition between native Antarctic vascular plants and invasive Poa annua changes with temperature and soil nitrogen availability - Cavieres, Lohengrin A.; Karen Sanhueza, Ana; Torres-Mellado, Gustavo; Casanova Katny, Angélica (Biological Invasions, 2021)
Over the last decades human have introduced non-native organisms to Antarctica, including the grass species Poa annua. This non-native grass under constant growth temperatures has been shown negatively affect the growth of the only two native Antarctic vascular plants, Deschampsia antarctica and Colobanthus quitensis, under constant growth temperatures. However, whether there are changes in the interaction between these species under warmer conditions is an important question. In cold ecosystems, soil nutrient status directly affects plant responses to increases in temperature and Antarctic soils are highly variable in nutrient supply. Thus, in this study we experimentally assessed the interaction between the non-native Poa with the two native Antarctic vascular plant species at two different temperatures and levels of nutrient availability. Individual mats of the study species were collected in King George Island, and then transported to Concepcion where we conducted competition experiments. In the first experiment we used soil similar to that of Antarctica and plants in competition were grown at two temperatures: 5 degrees/2 degrees and 11 degrees/5 degrees C (day/ night temperature). In a second experiment plants were grown in these two temperature regimes, but we varied nitrogen (N) availability by irrigating plants with Hoagland solutions that contained 8000 or 300 mu M of N. Overall, Poa exerted a competitive effect on Deschampsia but only at the higher temperature and higher N availability. At 5 degrees/11 degrees C the competitive response of Deschampsia to Poa was of similar magnitude to the competitive effect of P. Deschatnpsia, and the competitive effect was greater with at low N. The competitive effect of Poa was similar to the competitive response of Colobanthus to Poa at both temperatures and N levels. Thus, at low temperatures and N soil content the native Antarctic species might withstand Poa invasion, but this might change with climate warming.